The Semiclassical Limit of the Gailitis Formula Applied to Electron Impact Broadening of Spectral Lines of Ionized Atoms - Sylvie Sahal-Bréchot (Atoms, 2021)
The present paper revisits the determination of the semi-classical limit of the Feshbach resonances which play a role in electron impact broadening (the so-called “Stark“ broadening) of isolated spectral lines of ionized atoms. The Gailitis approximation will be used. A few examples of results will be provided, showing the importance of the role of the Feshbach resonances.